A new rigid diindolocarbazole donor moiety for high quantum efficiency thermally activated delayed fluorescence emitter - Kim, Kwang Jong; Kim, Gyeong Heon; Lampande, Raju; Ahn, Dae Hyun; Im, Joon Beom; Moon, Ji Su; Lee, Jae Kyun; Lee, Jae Yeol; Lee, Ju Young; Kwon, Jang Hyuk (ROYAL SOC CHEMISTRY, 2018)
In this communication, we report an excellent new highly conjugated and rigid electron donor (diindolocarbazole) for thermally activated delayed fluorescence (TADF) emitters. The donor-acceptor structure with diindolocarbazole donor induces high oscillator strength as well as high probability for the radiative transition, suitable frontier molecular overlap with proper intramolecular charge transfer and a large dihedral angle with out-of-plane structure between electron donor and acceptor; this results in high photoluminescence quantum yield, small singlet-triplet energy splitting, and extremely short delayed fluorescence exciton lifetime. The fabricated organic light emitting diode with new donor applied green emitter exhibits a remarkably high external quantum efficiency of 31.4% without any out-coupling technique. It also shows extremely low efficiency rolloff characteristics with the highest luminance of 71160 cd m(-2) as well as good operational device stability.
Keywords: LIGHT; DIODES; BLUE; DEVICES